Information System Design Based On Enterprise Resource Planning Using Account Payable Module Sap With ASAP Method In PT. Len Industri (Persero) - Husaini, Fachri; Putri, Debby Cintia Ganesha; Witjaksono, R.Wahjoe; Idawicaksakti, Maria Dellarosawati (International Journal of Innovation in Enterprise System, 2018)
Len Industries (Persero) experienced problems related to Accounts Payable in the accounting department as incompatibility and delays in the processing of data and information that flows every day from other parts related to Accounts Payable section and otherwise. This is caused by the information system on PT. Len Industries (Persero) has not integrated with one to another and still done with simple technology and recording manually. Therefore, has been designed of an ERP information system that supports the activities of recorded Accounts Payable(AP) module at PT.Len Industries (Persero). Design of the system is used the method of ASAP (Accelarated SAP). By using this method, the authors conducted an analysis of the business processes that are running on the company and analysis of business processes in SAP ERP application. Then based on the results of the gap/fit analysis, will performed design proposal and design of business processes to SAP applications that have been compared to the needs of the company. The results from this study is an SAP Accounts Payable system that has been design and integrated with the company needs can be easier for companies to conduct cross-section of the existing Accounting. Keywords— ERP, Accounts Payable, Accounting, SAP, ASAP